EVALUATING THE BIOCHEMICAL EFFECTS OF SUBLETHAL EXPOSURE TO GLUFOSINATE-AMMONIUM ON MODEL ORGANISM ZEBRAFISH (Danio rerio) TISSUES - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2021)
Pesticides are widely used chemicals in agriculture, but these chemicals reach aquatic animals and pollute their habitats. In our study, the effects of Glufosinate-ammonium, a widely used herbicide, on the liver and gill tissues of the zebrafish (Danio rerio), which is a model organism, were examined. Primarily, the dose that would kill fifty percent of these fish was determined. In the next step, zebrafish were exposed to sublethal doses (50 mg/L and 100 mg/L) for 120 hours. The effects of the herbicide on oxidative stress parameters were evaluated as enzymatic (Catalase-CAT and Acetylcholinesterase-AChE enzyme activity) and non-enzymatic (Glutathione-GSH, Malondialdehyde-MDA and Total Protein levels). In conclusion, MDA, Total Protein, GSH levels and CAT enzyme activities decreased at low dosing (50 mg/L) in laboratory conditions in zebrafish liver and gill tissues associated with oxidative stress, while it increased at high dosing (100 mg/L). AChE enzyme activity showed a similar picture in liver tissue, but increased in gill tissue at both doses. It can be said that the effect of Glufosinate-ammonium may increase depending on the dose and its presence may pose a serious threat to fish.
Keywords: Zebrafish; herbicide; oxidative stress; model organism